Paid Caregiver Communication With Homebound Older Adults, Their Families, and the Health Care Team. (21st May 2019) - Reckrey, Jennifer M; Geduldig, Emma T; Lindquist, Lee A; Morrison, R Sean; Boerner, Kathrin; Federman, Alex D; Brody, Abraham A
Abstract: Background and Objectives: Although paid caregivers (e.g., home health aides and home care workers) provide essential care for homebound older adults with serious illness in their homes, little is known about how and to whom paid caregivers communicate about the health needs they encounter. This study explored how paid caregivers (i) communicate when older adults experience symptoms or clinical changes and (ii) interact with the health care team. Research Design and Methods: We conducted separate one-on-one, semi-structured interviews ( n = 30) lasting 40–60 min with homebound older adults (or their proxies if they had cognitive impairment) and their paid caregivers (provided they had worked with the older adult for ≥8 hr per week for ≥6 months). Interviews were audio-recorded, transcribed, and coded. Results: Thematic analysis identified four themes: (i) older adults or their families were the gatekeepers to paid caregiver communication with the health care team; (ii) communication between older adults, their families, and paid caregivers was enhanced when close relationships were present; (iii) paid caregivers responded to health care team inquiries but rarely communicated proactively; and (4) most older adults, families, and paid caregivers were satisfied with existing paid caregiver communication with the health care team. Discussion and Implications: Rather than discuss concerns with the health care team, paid caregivers communicated directly with older adults or their families about the health needs they encounter. Understanding how communication occurs in the home is the first step to maximizing the potentially positive impact of paid caregivers on the health of older adults living at home.